THE DIFFERENCE OF PROBLEM BASED LEARNING MODELS & INFORMATION TECHNOLOGY-BASED SELF-DIRECTED LEARNING MODELS ON THE INDEPENDENCE AND LEARNING OUTCOMES - Laili Nur Rufaidah; Nurul Umamah; Sumardi Sumardi; Riza Afita Surya (History Education, University of Jember, 2020)
The 2013 curriculum is based on 21st century competence and character education. Independence is one of the main values in the character education of the Indonesian nation and the 21st skills are the vision of education to face technological advances and develop the various intelligences of students to achieve optimal learning outcomes. The purpose of this study was to investigate the differences in independence and learning outcomes of students who were taught using the Problem Based Learning model and students who were taught using the information technology-based Self-Directed Learning model. The results showed that there were significant differences in the independence and learning outcomes of students who were taught using the Problem Based Learning model and students who were taught using the information technology-based Self Directed Learning model in history subjects. The difference in the mean value of independence obtained is -4,265 and the mean value of learning outcomes obtained is -4,706 negative values indicate that the experimental class 2 which was taught using the information technology-based Self-Directed Learning model was better than the experimental class 1 which was taught with the PBL model (Problem Based Learning).